Three-rooted Maxillary and Bi-rooted Mandibular Primary Canines: A Case Report - Khashayar Sanjari; Hosna Ebrahimi Zadeh; Leila Eftekhar (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Multi-rooted primary canine is a rare anomaly in the primary dentition. The most common and normal form of root morphology in primary canines is a single root, while rare cases of bi-rooted or three-rooted canines have been reported in different ethnic groups. This anomaly is often discovered accidentally on routine radiographs. The anomaly often occurs bilaterally in the maxilla. This report presents a case of bilateral three rooted maxillary and unilateral bi-rooted mandibular primary canines in a four-year-old Iranian boy. This study aims to increase clinicians' awareness regarding this unique variation and emphasize the importance of radiological examination prior to root canal treatment.